Outpatient Use of Monoclonal Antibodies Casirivimab and Imdevimab in Pregnancy for Mild-to-Moderate Coronavirus Disease 2019 - Buonomo, Antonio Riccardo; Filippo, Isabella Di; Esposito, Nunzia; Saccone, Gabriele; Nobile, Mariano; Viceconte, Giulio; Villari, Riccardo; Carlo, Costantino Di; Bifulco, Giuseppe; Gentile, Ivan (American Journal of Perinatology, 2023)
Objective The aim of this study was to report the use casirivimab/imdevimab therapy in pregnant women with moderate coronavirus disease 2019 (COVID-19).Study Design We report 12 cases of unvaccinated pregnant patients with mild-to-moderate COVID-19 treated with casirivimab/imdevimab.Results Twelve unvaccinated pregnant patients with mild-to-moderate COVID-19 received casirivimab/imdevimab at the dose of 1200/1200 mg by intravenous infusion over 60 minutes. All women were managed outpatient. None experienced severe adverse drug reaction and none progressed to severe disease.Conclusion Casirivimab/imdevimab should be considered for outpatient treatment of unvaccinated pregnant women with mild-to-moderate COVID-19 to decrease the risk of severe disease.Key Points
Keywords: COVID-19; infection; NICU; preterm birth